Development Of E-LKPD With PNL Approach And Based On Jambi Culture To Improve Students' Mathematical Communication Skills - M Nasiruddin Fa; Jefri Marzal; Yantoro Yantoro; Alya Hanifah Setiawan; Hazar Kusmayanti; Sridewi Anggraeni Wiyono (PT Publikasiku Academic Solution, 2024)
The low mathematical communication skills of students should be the main issue that should be of concern to an educator. Learning should be designed through problems that allow students to be able to do better mathematical communication. This study aims to produce an E-LKPD with a Problem-Based Learning approach based on Jambi culture with valid, practical, and effective quality to improve students' mathematical communication skills. The subject of this research is class VIII MTsSBustanulUlum in even semester 2023/2024. This type of research is Research and Development with the ADDIE model. The results of this study indicate that the quality of E-LKPD developed has valid, practical, and effective categories. The validity can be seen from the results of expert validation in the field of media and learning materials which show that E-LKPD is good and feasible to use, practicality can be seen from the perceptions of students and teachers who give positive responses to the E-LKPD developed and effectiveness can be seen from the increase in students' mathematical communication skills by comparing the pree test and post-test scores with the N-Gain test with an acquisition of 0.50 with a moderate category. Thus to improve students' mathematical communication skills can use E-LKPD with a problem-based learning approach based on the Jambi culture that has been developed.